Influence of injury on the attitude of female students to further physical cul-tural classes - Semenova G.I. ,; Shikhov A.V. ,; Solomyanny A.V. ,; Starikova K.E. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to analyze the impact of a sports injury on the attitude of female university students to further volleyball training. Methods and structure of the study. A questionnaire was developed containing 21 questions, grouped into 3 blocks: the reasons for the injury and the player’s condition at the time of injury (6 questions), psychological state during the recovery period (5 questions) and attitude towards further sports activities (10 questions). Results and conclusions. The opinion of 148 UrFU students who experienced sports injuries, both professional volleyball athletes and unranked students who played volleyball in physical education classes, was studied. It has been established that in physical education classes the level of physical education injuries is quite high and in all respects (causes of injury, severity, location) is practically no different from sports injuries. Psychological changes and the formation of new behavioral models associated with the consequences of trauma in female athletes and sportswomen also generally coincide. However, a noticeable difference is the more severe and negative subjective reaction of female athletes to the injury. A comparative analysis of the attitude of female volleyball players to further activities after suffering an injury indicates a readiness to overcome its consequences by increasing self-control and stress resistance, regardless of the cause, location and severity of the injury. The university students are optimistic and plan to continue playing volleyball. When experiencing a situation of injury, female athletes, to a greater extent than female athletes, need help and psychological rehabilitation. A promising approach in this direction is to teach them methods of mental self-regulation, in particular, coping strategies.